Fishing boat construction : 4 : building an undecked fibreglass reinforced plastic boat - Anmarkrud, Thomas (FAO RomeIT, 2009)
Provides general basic knowledge in the use of fibreglass reinforced plastics (FRP), a boat building material. Sets out in detail step by step construction of a 4.5 m open fishing boat. Describes how to maintain an FRP boat and how to recognize fatigue problems.